HUBUNGAN PENGALAMAN MENYUSUI PADA IBU BERSALIN CAESAR DENGAN PENGETAHUAN PEMBERIAN ASI EKSKLUSIF DI RSUD Dr. H.ABDUL MOELOEK KOTA BANDAR LAMPUNG - Purwanggi, Annisa (Jurnal Kesehatan, 2022)
WHO stated that the average number of exclusive breastfeeding in the world in 2018 was 38%, which means that it still has not reached the target in the coverage of breastfeeding up to 80%. The coverage of breastfeeding is influenced by several factors. In Northwest Ethiopia, breastfeeding is influenced by the age of the baby, the mother's employment status, breastfeeding counseling during pregnancy visits, place of delivery, type of delivery and counseling on breastfeeding techniques. Cesarean deliveries are increasing worldwide, it exceeds the WHO range limit which exceeds up to 10% -15%. This type of research uses an analytical design with a cross sectional approach. This research was conducted in RSUD Dr. H. Abdul Moeloek Bandar Lampung City. This study was conducted in March 2021. The population used in this study were all mothers with caesarean delivery. Of the total population of 30 people. The sampling technique in this study is non-probability sampling, purposive sampling type. The criteria for sampling must meet several conditions that meet the inclusion and exclusion criteria. The inclusion criteria in this study are to provide respondents, mothers with caesarean deliveries, have a minimum education of elementary school. While the exclusion criteria in this study were mothers with normal delivery and mothers with caesarean deliveries who were not respondents. The tests carried out were univariate analysis and bivariate analysis. The bivariate analysis test used was the Chi-square test with a value of = 0.05. The results of the study obtained a value of = 0.042, which means that there is a relationship between the experience of caesarean delivery mothers and exclusive breastfeeding.